In Silico Design of Cylindrophanes: The Role of Functional Groups in a Fluoride Selective Host. Issue 17 (6th August 2020) - Østrøm, Ina; Ortolan, Alexandre O.; Caramori, Giovanni F.; Mascal, Mark; Muñoz‐Castro, Alvaro; Parreira, Renato L. T.
Abstract: Molecular recognition is the key driver in the formation of supramolecular complexes, enabling the selective encapsulation of specific guests. Here, we explore the delicate balance between different energetic terms in the formation of an efficient host for fluoride anions based on a cylindrophane structure, which can be achieved by the incorporation of ligand sites into a cyanuric acid based cyclophane framework, resulting a close proximity between the ammonium hydrogens and the anion. This study describes the character and contribution of different energetic and repulsive terms that favor the efficient inclusion of fluoride. Our findings are useful for further rational design and synthesis of efficient and highly selective fluoride hosts, which have been generally less well described than complexing agents for other halides. Abstract : This study describes systematically the character and contribution of different energetic and repulsive terms that favor the efficient inclusion of fluoride anion in a cylindrophane host, being helpful for the rational design and synthesis of efficient and highly selective fluoride hosts.